Lernwelt Hochschule gestalten (De Gruyter, 2024)
Managing universities, especially teaching, is complex. One requirement for success is interplay at all levels – between the ministry, management, lecturers, students, and administration. Grounded in empirical research, this volume presents the perspectives of different stakeholders, highlights challenges and potential areas for development within the university structure, and points to courses of action being taken in other European countries.